La eficacia constitucional en la prueba de alcoholemia y narcotest en materia de tránsito y seguridad vial - Torres Morocho, Nataly Itamar; Arias Hernández, Jean Pablo (Machala, 2022)
The objective of this study is to analyze the constitutional veracity on the scope of the breathalyzer test and narcotest in matters of traffic and road safety, so that the legal-legal parameters are complied with when practicing its usefulness. To this end, documentary research was applied, which is linked to the analysis and reflection of historical texts, legal instruments, journals or bibliographic sites of a scientific nature, necessary to corroborate the evaluation criteria, the principles related to the test, the procedure, the sanctions and doctrinal, legal and constitutional development that entails the realization of this test. Among the main results, it is highlighted that the civilian traffic agents at the time of proceeding to perform the breathalyzer and narcotest test must comply with the technical-scientific parameters, but in case the drivers refuse to take the test, psychosomatic tests will be practiced, the same ones that must be captured in audiovisual media, but this action will be of a reserved nature and may be reproduced only within the process, in addition, the right to the protected legal good, road safety, legal security and the presumption of innocence must be safeguarded. From what has been analyzed, it is concluded that the correct practice of the aforementioned evidence serves as a tool to avoid traffic accidents and if at the time of taking the test the traffic agent constitutes it as an element of conviction if it affects due process, but if it is only considered as investigative evidence it does not violate our constitutional rights.
El presente trabajo de estudio se plantea como objetivo analizar la veracidad constitucional sobre el alcance de la prueba de alcoholemia y narcotest en materia de tránsito y seguridad vial, de menara que se cumpla con los parámetros jurídicos-legales al momento de practicar su utilidad. Para ello se aplicó la investigación documental que está vinculada al análisis y reflexión de textos históricos, instrumentos jurídicos, revistas o sitios bibliográficos de índole científico, necesarios para corroborar los criterios valoración, los principios relacionado a la prueba, el procedimiento, las sanciones y desenvolviendo doctrinal, legal y constitucional que conlleva la realización de esta prueba. Entre los principales resultados se destaca que los agentes civiles de transito al momento de proceder a realizar la prueba de alcoholemia y narcotest deberá cumplir con los parámetros técnico-científicos, pero en caso de que los conductores se nieguen a realizarse la prueba se practicaran pruebas psicosomáticas las mismas que deben ser captada en medios audiovisuales, pero esta acción será de carácter reservada y se podrá reproducir solo dentro del proceso, además, se debe resguardar el derecho al bien jurídico protegido, la seguridad vial, seguridad jurídica y la presunción de inocencia. De lo analizado se concluye, que la correcta práctica de la prueba ya mencionada sirve como herramienta para evitar accidentes de tránsito y si al momento de realizar la prueba el agente de tránsito lo constituye como elemento de convicción si afecta el debido proceso, pero si se solo es considerada como indicios investigativos no vulnera nuestros derechos constitucionales.
Keywords: DEBIDO PROCESO; CONSTITUCIONALIDAD; IMPUGNACION; CONTRAVENCION